Thinking Outside the Researcher: The Imaginative Rewards of Participatory Analysis - Michelle Teti; Enid Schatz (International Journal of Qualitative Methods)
Community-Based Participatory Research (CBPR) is now commonplace in myriad disciplines from sociology to psychology to environmental science and health and medicine. In the context of my home discipline, public health, CBPR is a collaborative research approach where participants and researchers co-design projects and move them to action to improve health outcomes. CBPR occurs on a lengthy continuum from minor (e.g., community advisory boards) to major (e.g., community PIs) community engagement. Despite numerous and growing examples and varied ways of defining and discussing CBPR, many self-identified CBPR researchers agree that participatory analysis, where researchers and participants work together to evaluate data , is one of the most underdeveloped and least explored aspects of the research approach. Below I summarize the budding literature on participatory analysis, and then via case study, describe one lesser discussed reward of the co-analysis process – how participants can push the boundaries of research findings into new, unforeseen, and needed territories.